Non-Hodgkin’s Lymphoma in the Parotid Gland Similar to Benign Lymphoepithelial Lesion: A Case Indonesian Male - Muhammad Arif Sudianto Utama1 , Widodo Ario Kentjono2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Primary parotid non-Hodgkin’s lymphoma (NHL) is a very rare case. Case presentation: A66-year-old Indonesian male with a complaint of a lump in front of the right ear about 1 year with a history ofpostoperative primary parotid NHL 3 years ago. Patients underwent Fine Needle Aspiration Biopsy (FNAB)examination, showing a distribution of lymphoid cells with a diverse population (benign lymphoepitheliallesion / BLL) different from the results of FNAB 3 years ago. The patient underwent a right superficialparotidectomy, and the results of the histopathological examination revealed mature lymphocyte cells mixedwith histiocytes, forming foci of the follicle in part with an active germinal center. Conclusion: NHL reportsare necessary to minimize misdiagnosis between primary parotid NHL and BLL.